2023
DOI: 10.1093/mnras/stad572
|View full text |Cite
|
Sign up to set email alerts
|

Modelling supermassive primordial stars with mesa

Abstract: Supermassive stars forming at z ∼ 15–20 are one of the leading contenders for the origin of the first quasars, over 200 of which have now been discovered at z > 6. These stars likely form in pristine, atomically cooled haloes immersed in strong Lyman-Werner UV backgrounds or in highly supersonic baryon streaming flows. Atomic cooling triggers catastrophic baryon collapse capable of building up stars at rates of up to ∼1 M⊙ yr−1. Here we examine the evolution of supermassive stars with a much larger and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…The final stages of the formation of the DCBH have been explored in simulations up to the stage where supermassive stars (SMSs) are produced. Rapid baryon collapse at the center of atomically cooled halos has been demonstrated to produce SMSs (Hosokawa et al 2013;Woods et al 2017;Haemmerlé et al 2018;Herrington et al 2023) that are then predicted to collapse either by the post-Newtonian general relativity instability or from the depletion of core fuel at the end of post-main-sequence burning to form DCBHs. These simulations are yet to track the subsequent formation and growth of the BH seed and the stellar component in the host galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…The final stages of the formation of the DCBH have been explored in simulations up to the stage where supermassive stars (SMSs) are produced. Rapid baryon collapse at the center of atomically cooled halos has been demonstrated to produce SMSs (Hosokawa et al 2013;Woods et al 2017;Haemmerlé et al 2018;Herrington et al 2023) that are then predicted to collapse either by the post-Newtonian general relativity instability or from the depletion of core fuel at the end of post-main-sequence burning to form DCBHs. These simulations are yet to track the subsequent formation and growth of the BH seed and the stellar component in the host galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…Maiolino et al (2023) found 12 new AGN identified by the presence of broad emission lines at z > 4 in the JWST JADES survey. The BHs are a few times 10 5 -10 7 M e , less massive than quasars at the same redshifts but, interestingly, similar in mass at the low end to those expected for direct collapse black holes at birth (Hosokawa et al 2013;Woods et al 2017;Latif et al 2022b;Herrington et al 2023;Patrick et al 2023). They are overmassive relative to their host galaxies when compared to the local M BH -M star relation and their bolometric luminosities range from 10 44 to 10 45 erg s −1 .…”
Section: Introductionmentioning
confidence: 70%
“…5 pc (Begelman 2010). In the 1D simulations-imposing a spherical symmetry and hydrostatic equilibrium, as well as including the contribution of the H − opacity-this radius was claimed to reach 1.8 × 10 −3 pc (e.g., Hosokawa et al 2013;Haemmerlé et al 2019;Herrington et al 2023). For these models, the effective photospheric temperature of a bloated star was found to be less than 10 4 K. Therefore, its ionizing luminosity can hardly have an effect on its environment.…”
Section: The Properties Of the Central Mass Accumulationmentioning
confidence: 97%